Caffeoylquinic Acids from Aster tataricus Leaves Inhibit Aldose Reductase and Attenuate Hyaloid-Retinal Vasodilation in a Zebrafish Model of Hyperglycemia - Lee, Ik Soo; Jung, Seung-Hyun; Kim, Young Sook (Planta Medica, 2025)
Diabetic retinopathy (DR) is a leading cause of blindness, and its pathogenesis is strongly linked to the activation of aldose reductase (AR) under hyperglycemic conditions. Developing effective AR inhibitors (ARIs), particularly from natural sources, remains a critical therapeutic goal. This study investigated the AR inhibitory potential of an 80% ethanol extract from the leaves of Aster tataricus. Using UPLC-Q-Orbitrap-MS, we identified 11 major compounds, with caffeoylquinic acids (CQAs) being predominant. In vitro assays on rat lens aldose reductase (RLAR) revealed that di-caffeoylquinic acids (di-CQAs), particularly 3,5-di-O-caffeoylquinic acid (3,5-DCQA; IC50 = 0.31 µM), were potent noncompetitive inhibitors. Molecular docking simulations provided insights into their binding modes within the enzyme. The therapeutic relevance of these findings was confirmed in vivo using a larval zebrafish model of hyperglycemia, where both the A. tataricus extract and its constituent CQAs significantly suppressed hyaloid-retinal vessel dilation without inducing toxicity. Quantitative HPLC analysis confirmed that 3,5-DCQA was the most abundant di-CQA in the extract. These findings establish the CQA constituents of A. tataricus leaves as promising natural product leads for developing therapeutics to manage early-stage diabetic retinopathy.
Keywords: Aster tataricus; Asteraceae; caffeoylquinic acids; diabetic retinopathy; rat lens aldose reductase; zebrafish; molecular docking